2005
DOI: 10.1161/circulationaha.105.542209
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activity of the Myocardial Na + /H + Exchanger NHE-1 Contributes to Cardiac Remodeling in Atrial Natriuretic Peptide Receptor–Deficient Mice

Abstract: Background— Atrial natriuretic peptide (ANP), through its guanylyl cyclase-A (GC-A) receptor, not only is critically involved in the endocrine regulation of arterial blood pressure but also locally moderates cardiomyocyte growth. The mechanisms underlying the antihypertrophic effects of ANP remain largely uncharacterized. We examined the contribution of the Na + /H + exchanger NHE-1 to cardiac remodeling in GC-A–deficient (GC-A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
74
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 46 publications
6
74
1
1
Order By: Relevance
“…Recently, we demonstrated that transgenic expression of an activated form of NHE1 causes cardiac hypertrophy and heart failure due to activation of Ca 2ϩ -dependent prohypertrophic factors (e.g., CaN and Ca 2ϩ /CaM-dependent protein kinase II) via increased cytosolic [Ca 2ϩ ] and [Na ϩ ] (37). Indeed, there are many reports demonstrating that the expression level of NHE1 is elevated in various hypertrophic animal models (12,23,24). In the present study, we demonstrated that overexpression of NHE1 resulted in cardiomyocyte enlargement and augmented hypertrophic gene (ANF and RCAN1) expression.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Recently, we demonstrated that transgenic expression of an activated form of NHE1 causes cardiac hypertrophy and heart failure due to activation of Ca 2ϩ -dependent prohypertrophic factors (e.g., CaN and Ca 2ϩ /CaM-dependent protein kinase II) via increased cytosolic [Ca 2ϩ ] and [Na ϩ ] (37). Indeed, there are many reports demonstrating that the expression level of NHE1 is elevated in various hypertrophic animal models (12,23,24). In the present study, we demonstrated that overexpression of NHE1 resulted in cardiomyocyte enlargement and augmented hypertrophic gene (ANF and RCAN1) expression.…”
Section: Discussionsupporting
confidence: 70%
“…Activation of NHE1 is also involved in cardiac hypertrophy and heart failure, as shown by studies in animal models and isolated cardiomyocytes (10,12,21,37,53). The expression level of NHE1 was reported to be elevated in various hypertrophic animal models (12,24). Furthermore, we recently reported that, based on results using transgenic mice with activated NHE1, activation of NHE1 is sufficient for increasing prohypertrophic Ca 2ϩ signals, leading to cardiac hypertrophy and heart failure (37).…”
mentioning
confidence: 97%
“…39 Other molecules downstream of PKG also merit consideration for a role in the antihypertrophic action of natriuretic peptide/GC-A signal transduction. Recently, Kilic et al 40 reported that GC-A moderates cardiac growth response to pressure overload by preventing excessive activation of the Na ϩ /H ϩ exchanger NHE-1 and subsequent increases in Ca 2ϩ / calmodulin-dependent kinase II as well as Akt. This demon- Mechanism of GC-A-mediated inhibition of cardiac hypertrophy suggested from the findings of this and previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…82 Recently, a very interesting study reported that cardiac hypertrophy of atrial natriuretic peptide receptor-deficient mice was accompanied by an increased activity of NHE-1 with increased [Ca 2ϩ ] i . 83 Long-term treatment with the NHE-1 inhibitor cariporide normalized these alterations. 80 These results are in line with a report by Tajima et al, who demonstrated that atrial natriuretic peptide inhibits NHE-1 activity.…”
Section: The Nhe-1 In Myocardial Hypertrophymentioning
confidence: 97%
“…Interestingly, whereas long-term NHE-1 inhibition by cariporide in the whole animal induces upregulation of the exchanger, 103 the normalization of its previously augmented expression has also been reported after long-term NHE-1 inhibition. 74,75,83,89 Several aspects require further investigation to clarify the precise mechanism by which NHE-1 is involved in the development of cardiac hypertrophy and failure and its possible link with other intracellular signaling pathways. A disparate negative result about the antihypertrophic effect of NHE-1 inhibition in rats was reported by Loennechen et al, 104 who described a salutary effect of losartan on postinfarction remodeling and gene expression that was not shared by cariporide.…”
Section: The Nhe-1 In Myocardial Hypertrophymentioning
confidence: 99%